(untitled) (Communications in Computational Chemistry, 2025)
This work employed DFT calculations to elucidate the mechanism of water oxidation reaction catalyzed by a mononuclear pyridine-based copper complex, which was reported to be a homogeneous water oxidation catalyst in a pH=11.84 buffer solution. The coordination of one water molecule with the Cu^II center leads to the generation of the Cu^II -OH_2 (1-H_2O). The active species (Cu^IV =O, 3) is generated after two subsequent proton-coupled electron transfer processes from 1-H_2O. 3 triggers the O-O bond formation via water nucleophilic attack mechanism. The triplet O_2 can be released after following two oxidation processes. The formation of the O-O bond is the rate-determining step for the catalytic cycle associated with a total barrier of 19.3 kcal/mol.